The ethanolic extract of red cabbage (Brassica oleracea l. var,capitata f. rubra) in cream preparation to the dermal-thickness of male Wistar mice (Rattus norvegicus) after Ultraviolet-B exposure - Gayathiri Mohana Krishnan; IG Kamasan Arijana; I Wayan Sugiritama (Intisari Sains Medis, 2018)
Background: Photoaging effect in dermal layer of skin was commonly caused by Ultraviolet B (UV-B) rays exposure This study aims to assess the histological features of the dermis layer in the male Wistar mice after applied with the ethanolic extract of red cabbage following UV-B exposure.Methods: About 25 male Wistar rats were enrolled in this study by using post-test only control group design during 2 weeks. They were divided into 5 groups as follows: control group (P1), basic cream (P2), 5% ethanolic extract of red cabbage cream (P3), 10% ethanolic extract of red cabbage cream (P4), and 20% ethanolic extract of red cabbage cream (P5). The UV-B dosage used are 325 mJ/cm2 among groups prior to study. The dermis-elastic fiber thickness was assessed by Image Raster software. Statistical analysis was carried out using SPSS version 20 in measuring normality test, mean, and ANOVAResults: There was no statistically significant difference in the thickness of dermal layer among groups (P = 0.3). The mean of dermis thickness was 666.60±143.15µm in P5 group, followed by 651.19±189.18µm in P4 group, and 547.43±188.41µm, 544.76±100.67µm, and 504.10±129.40 µm in P3, P2, and P1 group respectively.Conclusion: There was no a significant difference among different dosage of the ethanolic extract cream of red cabbage to the thickness of dermal layer after UV-B exposure.